2011
DOI: 10.1007/s00421-011-1893-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of N-acetyl-cysteine and hyperoxia on erythropoietin production

Abstract: Previous studies in healthy subjects have shown an increase in erythropoietin (EPO) production after administration of N-acetyl-cysteine (NAC). These authors hypothesized that NAC increases intracellular reduced glutathione, decreasing reactive oxygen species and enabling EPO production. We investigated if EPO production could be stimulated with a single dose of NAC, after 90 min of pure oxygen breathing. Thirty-eight healthy volunteers were randomized into either the control (C) group or the NAC group, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
13
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 29 publications
3
13
0
Order By: Relevance
“…Compared to the placebo, the IHH protocol induced a transient reduction in [EPO] within the initial 8 h following the IHH protocol. Our results thus present further evidence against the existence of NOP and concur with the findings of Keramidas et al (2011), McGuire et al (2006, and Momeni et al (2011).…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…Compared to the placebo, the IHH protocol induced a transient reduction in [EPO] within the initial 8 h following the IHH protocol. Our results thus present further evidence against the existence of NOP and concur with the findings of Keramidas et al (2011), McGuire et al (2006, and Momeni et al (2011).…”
Section: Discussionsupporting
confidence: 95%
“…In particular, subsequent studies either did not find augmented EPO production following an acute normobaric hyperoxic exposure (McGuire et al 2006;Momeni et al 2011) or have even shown a suppressive effect on EPO production (Keramidas et al 2011). This is in line with the results of previous studies showing the suppression of erythropoietic activity following normobaric hyperoxia in humans (Kokot et al 1994a, b).…”
Section: Introductionsupporting
confidence: 76%
“…This theory conflicts with the reported O 2 -induced erythropoietic suppression in animals [5,6] and humans [7][8][9][10][11]. Keramidas et al [7] observed that a 2-h exposure to normobaric hyperoxia did not increase the production of [EPO] in healthy men during a single-blinded counter-balanced crossover investigation.…”
Section: Introductionmentioning
confidence: 92%
“…Thereafter, the plasma [EPO] levels appeared to resume their natural circadian rhythm [12,13]. Likewise, McGuire et al [10] and Momeni et al [11] failed to detect any significant differences in plasma [EPO] in healthy individuals after an acute O 2 breathing intervention.…”
Section: Introductionmentioning
confidence: 97%
“…Water immersion may also result in elevated EPO plasma levels in healthy humans [6]. The EPO suppressing effect of hyperoxia may be mediated by free radicals [3,23]. N-acetyl-cysteine, a free radical scavenger, administered before exposure to reactive oxygen species e. g., under hyperoxic conditions, has been shown to increase EPO concentrations after an initial drop after exposure [23].…”
mentioning
confidence: 99%